Association between serious psychological distress and nonparticipation in cancer screening and the modifying effect of socioeconomic status: Analysis of anonymized data from a national cross‐sectional survey in Japan. Issue 3 (27th October 2017) - Fujiwara, Masaki; Inagaki, Masatoshi; Nakaya, Naoki; Fujimori, Maiko; Higuchi, Yuji; Kakeda, Kyoko; Uchitomi, Yosuke; Yamada, Norihito
Abstract : BACKGROUND: It is unclear whether individuals who have serious psychological distress (SPD) are less likely to participate in screening tests for gastric cancer, lung cancer, and other types of cancer. Of the few studies that have examined the association between SPD and participation in cancer screening, none have reported modifying effects of educational, marital, or employment status. METHODS: The authors analyzed a national representative data set from the 2010 Comprehensive Survey of Living Conditions of Japan., including individuals aged <69 years who met the national program criteria for each type of cancer screening (colorectal, gastric, and lung cancers, n = 29, 926; breast cancer, n = 15, 423; and cervical cancer, n = 24, 735). SPD was defined as a score of 13 or greater on the Kessler 6 scale. Logistic regression analyses were conducted to examine the association between SPD and participation in cancer screening, and multivariate analyses stratified by socioeconomic status also were conducted. RESULTS: SPD was significantly associated with a lower odds ratio (OR) for participation in screening for colorectal cancer (OR, 0.743; 95% confidence interval [CI], 0.638‐0.866), gastric cancer (OR, 0.823; 95% CI, 0.717‐0.946), and lung cancer (OR, 0.691; 95% CI, 0.592‐0.807). Only educational status significantly modified the effect of SPD on participation in these 3 types of cancer screening ( P  < .05). CONCLUSIONS: Individuals with SPD, especially those with lower education levels, were less likely to participate in screening for colorectal, gastric, and lung cancers. Individuals with SPD should be encouraged and supported to participate in cancer screening tests. Cancer 2018;124:555‐62. © 2017 American Cancer Society . Abstract : Individuals with serious psychological distress, and particularly those who have lower levels of education, are less likely to participate in colorectal, gastric, and lung cancer screening. Those who have serious psychological distress should be supported to access cancer screening.